Impact Evaluation of Food for Education Program in Bangladesh, 2000 - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The Impact Evaluation of Food for Education (FFE) survey was conducted in Bangladesh in 2000 to evaluate the effect of a conditional transfer of food to poor families that was designed to increase school attendance. The survey covered 600 households in 60 villages in 30 unions in 10 thanas, and 110 schools in the same 30 unions from which the household sample was drawn. Ten thanas were first randomly selected with probability proportional to size (PPS), based on thana-level population data from the 1991 census, and two FFE unions and one non-FFE union were selected per thana. From each union, two villages were randomly selected with PPS using village-level population data from the 1991 census. Because the focus of the FFE program was on economically disadvantaged areas, the sample of non-FFE unions was also selected from neighboring economically disadvantaged areas. This means that the subsequent sample cannot be regarded as representative of rural Bangladesh as a whole, but it does broadly characterize the conditions in the poorest upazilas in the country. A complete census of the households was then carried out in each of the selected villages, and ten households that had at least one primary-school-age child (6 to 12 years old) were randomly selected in each village from the census list of households. The 2003 survey is also available from IFPRI's website at Comparing Food versus Cash for Education Program in Bangladesh.